2015
DOI: 10.1589/jpts.27.1971
|View full text |Cite
|
Sign up to set email alerts
|

Changes in falling risk depending on induced axis directions of astigmatism on static posture

Abstract: [Purpose] To assess the changes in falling risk depending on the induced axis direction of astigmatism using cylindrical lenses in a static posture. [Subjects and Methods] Twenty subjects (10 males, 10 females; mean age, 23.4 ± 2.70 years) fully corrected by subjective refraction participated. To induce myopic simple astigmatism conditions, cylindrical lenses of +0.50, +1.00, +1.50, +2.00, +3.00, +4.00, and +5.00 D were used. The direction of astigmatic axes were induced under five conditions with increased cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…Moreover, Luna et al demonstrated that the Journal of Ophthalmology differences in lower and upper visual field loss in patients with glaucoma did not constitute balance functions differences [27]. On the other hand, refraction disorders such as uncorrected astigmatism and conditions affecting visual acuity, visual field, and contrast sensitivity like cataract also affect postural stability [28,29]. In our study, we thought that improved viral field and the directly associated improvements increased postural stability and could improve quality of life.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, Luna et al demonstrated that the Journal of Ophthalmology differences in lower and upper visual field loss in patients with glaucoma did not constitute balance functions differences [27]. On the other hand, refraction disorders such as uncorrected astigmatism and conditions affecting visual acuity, visual field, and contrast sensitivity like cataract also affect postural stability [28,29]. In our study, we thought that improved viral field and the directly associated improvements increased postural stability and could improve quality of life.…”
Section: Discussionmentioning
confidence: 55%
“…In a previous study 22 ) , visual blur induced by refractive errors was found to increase the FI. The FI value is especially higher in diagonal blur, which is induced by the incorrections of the oblique astigmatism more than the other blurs induced by the incorrections of the “with-the-rule” or the “against-the-rule” astigmatism while in stationary fixation in a static posture.…”
Section: Discussionmentioning
confidence: 69%
“…[18][19][20] Other than neurological problems, visual impairments can also affect postural stability and increase FI during posturographic examination. [23] A study investigating the effect of hemodialysis on balance found the FI score to be significantly higher after hemodialysis and they emphasized the risk of falling in all age groups of patients with renal insufficiency following hemodialysis. [24] On the other hand, Akdeniz et al [25] highlighted the importance of hypovitaminosis of vitamin D for risk of falling.…”
Section: Discussionmentioning
confidence: 99%